Pemanfaatan Artificial Intelligence Dalam Mengukur Kinerja Ruas Jalan Margonda Raya Kota Depok - Suardika, Bayu; Malkhamah, Siti; Rizka Fahmi Amrozi, Mukhammad (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
Jalan Margonda Raya is a primary collector road in Depok City that plays a vital role in urban traffic movement. The high volume of vehicles, especially during peak hours, often leads to significant congestion. This study aims to analyze traffic performance on the road segment based on the Indonesian Highway Capacity Guidelines (PKJI, 2023) and to evaluate the application of Artificial Intelligence (AI) in traffic surveys to improve data accuracy and minimize bias commonly found in conventional methods. The survey was conducted on weekdays, and the analysis showed that the highest traffic volume reached 4,161 pcu/hour, with a total vehicle count of 10,465 pcu/hour and an average speed of 31 km/h. The degree of saturation (DS) was recorded at 0.90, indicating a Level of Service (LOS) E—an unstable traffic condition approaching maximum capacity. The peak traffic period occurred between 06:45 and 07:45 AM. The implementation of AI in traffic surveys proved to deliver efficient and reliable results, offering an innovative alternative to support decision-making in transportation planning.